Organic dyes containing a hydrazone moiety as auxiliary donor for solid-state DSSC applications. (March 2015) - Urnikaite, Simona; Daskeviciene, Maryte; Send, Robert; Wonneberger, Henrike; Sackus, Algirdas; Bruder, Ingmar; Getautis, Vytautas
Abstract: D-D-π-A architecture metal-free organic dyes, containing a hydrazone moiety as an auxiliary donor were designed and synthesized for solid-state dye-sensitized solar cells. The sensitizer series was designed to develop a structure-property relationship. These dyes were obtained from the relatively cheap starting materials, without the use of expensive catalysts, rigorously anhydrous or oxygen-free conditions. The highest solid-state device conversion efficiency 3.9% ( J SC = −7.9 mA cm −2, V OC = 760 mV) and fill factor 0.65 under 100 mWcm −2 (AM 1.5G) solar irradiation were achieved with the dye D3 containing a methoxy group attached to the triphenylamine donor unit employed between the hydrazone moiety and rhodanine acceptor of the sensitizer. Highlights: D-D-π-A architecture metal-free organic dyes for solid-state DSSCs have been synthesized. The sensitizer series was designed to develop a structure-property relationship. Dyes are obtained using cheap starting materials and simple synthetic procedures. Solid-state dye-sensitized solar cells have been constructed. The best overall conversion efficiency of solid-state device was 3.9%.